Dermoscopy of skin metastases in advanced cancer—systemic (visceral, hematologic) and cutaneous - Simionescu, Olga; Petrică, Marian; Avram, Alina Mariana; Costache, Mariana; Scurtu, Lucian G.; Tudorache, Sorin Ioan; Iorga, Polixenia Georgeta; Grigore, Mariana (Frontiers in Medicine, 2024)
Introduction Skin metastases arise in 10% of cancer patients, but standardized dermoscopy diagnostic criteria for skin metastases remain poor. This study's objective was to analyze the dermoscopy features of skin metastases from advanced systemic and cutaneous cancers. Methods A retrospective study on 715 dermoscopy images of skin metastases from 33 patients with various primary cancers (breast, ovary, melanoma, non-melanoma skin cancer, and chronic leukemia) attending two academic centers between 2013 and 2023 was performed. Four independent observers blindly analyzed patterns, colors, vessels, and elementary lesions for each metastasis (30 parameters in total). Results The structureless white pattern was the most prominent indicator of cutaneous metastasis (81.26%, p < 0.001). Regardless of the primary tumor, colors pink, red, white, and tan were identified. Elementary lesions were infrequent, except for melanoma metastases that displayed dots (13.23%) and globules (11.11%). Breast cancer metastases presented: blue (41.48%) and red (34.32%) colors, irregular vessels (13.58%), and a blue-naevus pattern (22.22%). Melanoma metastases displayed: a blue-naevus pattern (61.38%), a blue color (85.71%), and a structureless-blue combination pattern (79.37%). Non-melanoma skin cancer metastases were characterized by vascular (42.11%) and angioma-like (31.58%) patterns, pink (57.89%) and red (57.89%) colors, irregular (57.89%), thin hairpin (47.37%), comma (47, 37%), and thick hairpin (26, 32%) vessels and a red, white and irregular vessels combination pattern (52, 63%). A pink structureless combination pattern was frequent (61.05%) in chronic leukemia metastases. Ovarian cancer metastases displayed a white and tan structureless combination pattern (100%) and frequently had dotted vessels (42.85%). Conclusion Papules and nodules with a white structureless pattern suggest skin metastases, regardless of the primary tumor. A blue structureless lesion is indicative of melanoma metastasis and a vascular pattern with irregular vessels indicates a non-melanoma skin cancer metastasis. Dermoscopy stands as a reliable non-invasive diagnostic method for suspected cutaneous metastases in patients with a known cancer history.